Intracranial germinoma metastasizing via aventriculo-peritoneal shunt - Wong, K.T.; Koh, K.B.H.; Lee, S.H.; Chee, C.P. (Faculty of Medicine, University of Malaya, 1996)
Primary germinomas of the central nervous system carry a good prognosis because of their radiosensitivity. Recurrences are rare and extraneural metastases are even more unusual. One of the possible routes of extraneural spread is via ventriculo-peritoneal shunts which may be required to reduce intracranial pressure. One such case of germinoma metastasizing via a ventriculo-peritoneal shunt is reported. Patients with intracranial germinomas and ventriculo-peritoneal shunts should have close surveillance of their abdomens and may require systemic chemotherapy.